A Comparison of Higher-Order Thinking between the Common Core State Standards and the 2009 New Jersey Content Standards in High School - Sforza, Dario; Tienken, Christopher H; Kim, Eunyoung (AASA journal of scholarship & practice, 2016)
The creators and supporters of the Common Core State Standards claim that the Standards require greater emphasis on higher-order thinking than previous state standards in mathematics and English language arts. We used a qualitative case study design with content analysis methods to test the claim. We compared the levels of thinking required by the Common Core State Standards for grades 9-12 in English language arts and math with those required by the New Jersey Core Curriculum Content Standards in grades 9-12 English language arts and math (used prior to the Common Core) using Webb's Depth of Knowledge framework to categorize the level of thinking required by each standard. Our results suggest that a higher percentage of the 2009 New Jersey high school curriculum standards in English language arts and math prompted higher-order thinking than the 2010 Common Core State Standards for those same subjects and grade levels. Recommendations for school administrative practice are provided.